Fabrication of proton-conducting yttrium-doped barium zirconate electrolytes for solid oxide fuel cells - Ng, Jerome Jian Peng (2014)
Proton-conducting Solid Oxide Fuel Cells (H-SOFCs) have seen an increase in its popularity due to its relatively low operating temperatures, as compared to other types of fuel cells. Of the different materials selected as the electrolyte for the H-SOFCs, the one that has retained its popularity to date is yttrium-doped barium zirconate (BZY).